Ideal Government Policy In Fulfilling The Social and Cultural Economic Rights of Sangir Philippine Citizens - Gerungan, Lusi K. F. R.; Lewerissa, Yanti Amelia; Atmodjo, Kevin Christian (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Fulfillment of economic, social and cultural rights is a reflection of guaranteeing human rights. However, the economic, social and cultural rights of every citizen must be supported by their status as a citizen. Because a person's citizenship status has the effect of giving them a number of rights as a citizen. This problem occurs for Sangir Filipino residents whose citizenship status is unclear.Purposes of the Research: Is to examine and analyze the ideal policies taken by the government, especially the regional government of Bitung City, North Sulawesi Province, in addressing issues that provide economic, social and cultural rights for Sangir Filipino residents who have unclear citizenship status, so that this has an impact. on Providing their rights as part of providing human rights.Methods of the Research: In this research is normative juridical research using statutory regulations and a contextual approach. The sources of legal materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. This legal material was obtained through literature review and then explained qualitatively.Results of the Research: Show that the citizenship status of Sangir Filipino residents does not clearly have an impact on the provision of economic, social and cultural rights. There is a need for policies by the Regional Government and the Central Government, such as updating national laws that simplify the citizenship registration process, providing outreach to Sangir Filipino residents about the importance of a clear citizenship status, and the need for participation from all elements of society in order to overcome this problem.